Challenges in Complex Oncological Chest Wall Reconstruction with Free Anterolateral Thigh Flap and Titanium Rib Plate - Chai, Cheng Siew; Shamugam, Kasthuri; Basiron, Normala Binti; Zain, Mohammad Ali Bin Mat; Zainal, Hamidah Binti; Luen, Koh Khai; Sathiamurthy, Narasimman; Chai, Diong Nguk; Pandian, Benedict Dhamaraj A.L. Retna (Indian Journal of Plastic Surgery, 2023)
Extensive chest wall tumor resection and reconstruction possess a formidable challenge and require good collaboration between thoracic and reconstructive surgeons. In this article, we reviewed our experience in six consecutive cases requiring complex chest wall resection and reconstruction with titanium rib plates and free anterolateral thigh fasciocutaneous flap with fascia lata with a minimum 24 months follow-up postoperatively.Six patients with a mean age of 54 were diagnosed to have locally advanced malignant (n = 5) and benign (n = 1) tumors. They underwent wide local excision with a mean of six ribs resected, and the average size of the soft tissue defect was 389cm2. The integrity of the thoracic cage was restored by using titanium rib plates. Fascia lata was harvested along with free anterolateral thigh fasciocutaneous flap to achieve near airtight closure of pleural space for soft tissue coverage. Two patients required early flap exploration with successful flap salvage. One flap failure was reported on postoperative day 11 due to a mechanical cause and a redo surgery was required. With an average stay of 3 days in the intensive care unit, no perioperative pulmonary complications were recorded.Complex oncological chest wall resection and reconstruction with titanium rib plates and free anterolateral thigh fasciocutaneous flap with fascia lata yielded satisfactory aesthetic and physiological functional outcomes.
Keywords: oncological chest wall reconstruction; anterolateral thigh flap; titanium rib plate